Study Analysis of Knowledge Mother and Environmental Conditions of Occurrence of Acute Respiratory Infections in Children - Dan Marniati, Yarmaliza (International Journal of Engineering and Technology, 2018)
Acute Respiratory Infections still menjdi major health problem in the world. According to the World Health Organization estimates that the incidence of acute respiratory infection in developing countries with under-five mortality above 40 per 1,000 live births is 15% - 20% per year in the toddler age group. About 13 million children under five in the world die each year and most of these deaths are in developing countries. Panga in the health center of the top 10 diseases, acute respiratory infections ranked first in the amount of 65% by the sheer number of infants 158. The aim of research to influence knowledge megetahui Mother and environmental conditions on the incidence of acute respiratory infections in Toddlers in Panga sub-district Puskesmas Panga Aceh Jaya 2014. this study is a descriptive analytic with cross sectional approach. The sampling technique using random sampling techniques, selected at random from each member of the population, an analysis of the data in this study using univariate and bivariate. The survey results revealed that mother's knowledge and environmental conditions affect the incidence of ARI in Toddlers (P <0.05).Â Â